The candidates’ beliefs in 2016 U.S presidential election debate through presupposition - Ayang Winda (Concept : Community Concern for English Pedagogy and Teaching, 2021)
The objectives of the study are to describe and analyze the types of presupposition and the belief of those candidates. This study utilizes qualitative descriptive method. The writer picked archive document analysis research procedure in breaking down the information. This research applied the types of presupposition by Yule (1996) and Belief by Van Dijk (1998). The analysis showed that there are six types of presuppositions such as: Existential, Factive, Lexical, Structural, Non-Factive and Counter-Factual Presupposition. When delivering their belief, both candidates using conjunction, context, coherence and also cohesive. First candidate’s belief, Hillary Clinton, showed her personal beliefs because Hillary knew everything how to be a president, how to lead the country, how to work with other country and how to get new jobs to make American be better because Hillary had sufficient experience. Apart from that, Hillary takes the name of President Obama to strengthen the belief that all people have more confidence in her because she presents the facts in accordance with the actual situation. While, the second candidate, Donald Trump examines social beliefs because he explores what happens to their country, including the greatest financial crisis. Donald claims of his own great deeds as a result that had given birth certificates for president. Besides, Donald also claimed that Hillary who had experience as the secretary of the state was not so astute in leading this country and it was evident from the phenomenon occur, many failures made by the present government that making a loss for the country. Keywords: belief, presupposition, presidential election